Rancang Bangun Sistem Informasi Persediaan Barang Pecah Belah Berbasis Web (Studi Kasus Toko Podomoro) Dengan Metode Fifo Dan Lifo - Patriya, Angga Prayoga; Harahap, Syaiful Zuhri; Juledi, Angga Putra (Jurnal Informatika, 2024)
Toko Podomoro is a glassware store that requires a fast and accurate data processing information system to facilitate the work. In modern times like today, Podomoro stores still use recording on books that have not been computerized. Purchase of goods and expenditure of goods is still manual by recording the data of incoming goods and goods out of the warehouse, hence the frequent occurrence of errors in the processing of incoming and outgoing goods data. While making a report that will be made is also still using expenditure records manually by writing in the book, not to mention the record of the purchase of lost goods, which is very important because of the evidence of the reports made. Therefore, it is necessary to have a system of goods investment in Podomoro stores to make it easier for store owners to input goods and stock reports, purchase and expenditure reports.